Design, implementation and evaluation of a program for teaching residents teaching skills at the Department of Obstetrics and Gynecology UP-PGH - Gonzales-Germar, Erlinda F. (1986)
Residents at the UP-PGH Medical Center assume a major responsibility in clinical teaching yet little attention has been directed towards systematic development of effective teaching skills. As a response to this need for developing residents' clinical teaching skills, a twelve week training program was designed and implemented. The course design utilized lecturettes small group discussions, instructional modules, and video recordings using the micro-teaching method. Significant gains in the chosen teaching skills were demonstrated by the 12 residents who participated in the study, based on the statistically significant changes in their mean scores in the skills ratings scales for their videotaped and actual performances and the results of a post program questionnaire. This indicates that short training programs during residency can assist physicians in the process of improvement of instructional skills.
Special project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Obstetrics -- Study and teaching (Residency); Gynecology -- Study and teaching (Residency)